The Effect of Work Relationships and Work Environment on Employee Performance at Pt. Karya Kasih Sentosa - Marsella, Prasastiara Eka; Insani, Wildan Nur (East Asian Journal of Multidisciplinary Research, 2024)
Research at PT Karya Kasih Sentosa aims to analyze the effect of work relationships and work environment on employee performance, both in the office and the field. Using an associative quantitative approach, this research was conducted from March to May 2023 by collecting data through questionnaires filled out by 30 respondents. The analysis shows that the variables of work relationship (X1) and work environment (X2) each have a positive and significant influence on employee performance, with t-count values of 5.430 and 2.343, both of which are greater than the t-table of 1.703. The simultaneous regression results state that the equation of the influence of the two variables is Y = 1.086 + 0.663 X1 + 0.269 X2, with an F-count value of 46.873 which is greater than the F-table of 3.37. The coefficient of determination of 0.776 shows that work relations and the work environment together affect employee performance by 77.6%.